Political connections, allocation of stimulus spending, and the jobs multiplier - Joonkyu Choi; Veronika Penciakova; Felipe Saffie (Federal Reserve Bank of Atlanta, 2021)
Using American Recovery and Reinvestment Act (ARRA) data, we show that firms lever their political connections to win stimulus grants and that public expenditure channeled through politically connected firms hinders job creation. We build a unique database that links information on campaign contributions, state legislative elections, firm characteristics, and ARRA grant allocation. Using exogenous variation in political connections based on ex-post close elections held before ARRA, we causally show that politically connected firms are 38 percent more likely to secure a grant. Based on an instrumental variable approach, we also establish that a one standard deviation increase in the share of politically connected ARRA spending lowers the number of jobs created per 1 million spent by 7.1 jobs. Therefore, the impact of fiscal stimulus is not only determined by how much is spent, but also by how the expenditure is allocated across recipients.
Keywords: D22; D72; E62; H57; P16; 330; campaign finance; state grants; public expenditure allocation; American Recovery and Reinvestment Act